Green Innovation in Batik Production as a Sustainability Strategy for MSMEs: A Case Study of the Batik Seng Program - Sinki Anggriani; Dian Karisma Septiana Guteres; Edi Purnomo; Raden Sultani Indragunawan (Pelopor Publikasi Akademika, 2026)
The conventional batik production process often causes environmental problems, particularly due to liquid waste and the use of synthetic chemicals, while support from Corporate Social Responsibility (CSR) programs can play an important role in encouraging sustainable business practices at the local level. This research aims to analyze green innovation in batik production as a sustainability strategy for Micro, Small, and Medium Enterprises (MSMEs) in the Batik Seng Program of Sengguruh Village. The program is part of the CSR initiative implemented by PT PLN Nusantara Power UP Brantas, which focuses on community empowerment through the development of the batik creative industry. The innovations introduced include the use of recycled batik wax and natural dyes as part of a clean production approach. This study employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation. The findings reveal that environmentally friendly innovation not only reduces environmental pollution but also increases product added value, expands market opportunities, and strengthens the group’s economic and social sustainability. These innovations have become an important strategy for maintaining the competitiveness of village-based MSMEs.